CRITICAL DISCOURSE ANALYSIS: EXPERIENTIAL FUNCTION OF THE OPEN UNIVERSITY ELEARNING CLASSROOM - Rakhmat Wahyudin Sagala (Kajian Linguistik dan Sastra, 2021)
The transition from face-to-face to online education might be delayed not just by the needed computer abilities, but also by shifting self-concept requirements for instructors. The goal of this study was to expand existing knowledge of the phenomena of Critical Discourse Analysis (CDA) in e-learning classrooms that emphasize experiential function. The subjects were undergraduate students of the English Department who enrolled in Indonesia Open University elearning classroom. The objectives of the study are : 1) to identify the types of discourse in experiential function used by tutor online and students ; 2) to analyze the experiential function used by tutor online in elearning classroom ; 3) to investigate the types of discourse in experiential function dominantly used by tutor online and students. Descriptive qualitative research was implemented to reveal the data from discourse of online tutor and students in e-learning classrooms. The finding provides tutor online and students perform experiential function in their discourse in the process of teaching-learning in the classroom. There were 35 clauses found in the discourse including process, participants, and circumstances. Types of experiential function used by online tutor and students of Indonesia Open University were 1) Participant such as Actor, Goal, Senser, Phenomenon, Possessor, Possessed, Sayer, Verbiage and Carrier, 2) Process such as Material, Mental, Relational and Verbal, 3) Circumstance such as Location, Manner, Cause and Matter. More specifically, critical discourse analysis exists and incorporates textually and contextually communication signals. Hence, online tutors and students frequently employ some forms of experiential function in their e-learning conversations. Keywords: critical discourse analysis, experiential function, categories of experiential function, e-learning classroom, Indonesia Open University